Changing pattern of biliary complications in an evolving liver transplant unit. Issue 4 (April 2017) - Rammohan, Ashwin; Govil, Sanjay; Vargese, Joy; Kota, Venugopal; Reddy, Mettu S.; Rela, Mohamed
Abstract : Biliary complications (BCs) remain a significant cause of morbidity following liver transplantation (LT). This series of 640 LT recipients with a blend of living and deceased donor transplants was analyzed to determine the incidence, risk factors, management protocol, and outcomes in these patients. Review of a prospectively collected database of transplant recipients operated between August 2009 and June 2016 was performed. Patients were divided into those with and without BCs and data analyzed. The 640 LT recipients from both living (n = 481) and deceased donors (n = 159) were evaluated for BCs. The overall incidence of BCs was 13.7%. It reduced from 23% to 5% ( P = 0.003) over a 6‐year period. Risk factors for BCs on multivariate analysis were living donor liver transplantation, prolonged time to rearterialization, recipient age above 16 years, prolonged cold ischemia time (CIT) after deceased donor liver transplantation, and biliary reconstruction performed by anyone but the senior author. One‐fifth of bile leaks progressed to strictures, and 40% of strictures followed leaks. Endoscopic therapy resolved 60% of the strictures. Surgical repair of strictures was successful in 90% of those in whom endoscopy failed, those who could not undertake the follow‐up schedules endoscopic therapy entails, and those presenting with late strictures. BCs significantly prolonged hospital stay but did not alter survival after LT. BCs affect 1 in 7 recipients, although they are not associated with increased mortality. The frequency of these complications is influenced by potentially modifiable factors like evolving surgical expertise and CIT. Liver Transplantation 23 478–486 2017 AASLD.